Correlation Between Reading Interest and News Text Writing Skills of Grade VII Students of SMP Negeri 24 Padang - Azzurra Azhari; Dadi Satria; Ayu Gustia Ningsih; Mita Domi Fella Henanggil (Raja Zulkarnain Education Foundation, 2026)
Reading interest is a source of motivation that encourages individuals to carry out activities to obtain information from written sources while news text writing skills are activities to express ideas in writing using the structure of orientation, events, and information about 5W + H. This study aims to describe: 1) the reading interest of seventh grade students of SMP Negeri 24 Padang; 2) the news text writing skills of seventh grade students of SMP Negeri 24 Padang; 3) the correlation between reading interest and news text writing skills of seventh grade students of SMP Negeri 24 Padang. This type of research is quantitative with a correlational research design. This research took place in the 2025/2026 academic year. The population of this study was all seventh grade students of SMP Negeri 24 Padang in 2025/2026, totaling 255 people. Sampling in this study was determined using a cluster sampling technique set at 24%, namely 61 students. Reading interest data in this study were collected using a reading interest questionnaire containing statements related to reading interest. Data on news text writing skills were collected using a test instrument in the form of giving students assignments to create news texts with a predetermined theme. Data on reading interest were analyzed using descriptive statistics. Data on news text writing skills were also analyzed using descriptive statistics. The correlation between reading interest and news text writing skills was analyzed using Spearman's correlation. The results of the study: 1) the reading interest of seventh grade students of SMP Negeri 24 Padang is in good qualifications; 2) the news text writing skills of seventh grade students of SMP Negeri 24 Padang are in good qualifications; 3) the correlation between reading interest and news text writing skills only produces r = 0.699; included in a high relationship; the coefficient of determination is 48.86 percent.